2021
DOI: 10.3390/ijerph18052291
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of the Acidophilic Microalgae Galdieria phlegrea with Wastewater: Process Yields

Abstract: Algal based wastewater treatment offers the opportunity to recover, in the form of biomass, the nutrients and internal chemical energy of wastewater. Recently, there has been a growing interest in the use of extremophilic microalgae, as they can easily adapt to difficult and often pollutant-rich environments. The thermo-acidophilic microalga Galdieria phlegrea is a species of recent discovery and great metabolic versatility, but it has still been poorly studied. Here, G. phlegrea was cultivated using raw munic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…The temperature range for freshwater algal growth, regardless of the strain, is typically between 15 and 30 • C (optimal of 20-25 • C). Some thermophilic strains can withstand higher temperatures of up to 56 • C and some psychrophilic strains can live in environments with temperatures of 17 • C [8,25,76,79,99,100]. Generally, the algal activity significantly drops (in some cases with more than 90%) with temperatures under 15 • C, leading to decreased nutrient removal efficiency and removal rate retardation [8,25,76,79].…”
Section: Temperature Controlmentioning
confidence: 99%
“…The temperature range for freshwater algal growth, regardless of the strain, is typically between 15 and 30 • C (optimal of 20-25 • C). Some thermophilic strains can withstand higher temperatures of up to 56 • C and some psychrophilic strains can live in environments with temperatures of 17 • C [8,25,76,79,99,100]. Generally, the algal activity significantly drops (in some cases with more than 90%) with temperatures under 15 • C, leading to decreased nutrient removal efficiency and removal rate retardation [8,25,76,79].…”
Section: Temperature Controlmentioning
confidence: 99%
“…In the specific case study of the Agropoli WWTP, as can be seen from the data shown in Table 3, the urban wastewater is characterized by an average temperature of about 22 • C and an average sub-acid pH (5,7). A wastewater with these values, used in an enclosed environment (e.g., greenhouse) and with a further non-invasive acidification (up to pH 4) could potentially be suitable for the use with extremophilic thermoacidophilic microalgae, which are currently among those of greatest interest on the market for their great adaptive capacity, tolerance to heavy metals and toxic substances in the environment, high productivity of bio-compounds with high market value (phycobiliproteins, pigments, glycogen and other reserve carbohydrates, secondary metabolites with antioxidant and antibacterial activity) [14,[36][37][38].…”
Section: O 2 Ph Tmentioning
confidence: 99%
“…The use of these practices, however, is still at a testing stage in most of the realities that have chosen to adopt these solutions for the increase of their performance indices [13]. Therefore, since it is not always possible to adopt this type of sustainable solutions, in order to improve the energy-environmental performance of these systems, it is still essential to optimize the use of energy within the facilities, through system auditing and the accurate monitoring of process variables [14]. The first tool is the one that allows to gather all the qualitative and quantitative information on the observed system in order to firstly frame its operating conditions and overall performance, based on data collected offline (static data) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, biological methods have been developed to ensure the recovery of small quantities of these metals from wastewater systems [5], using mainly bacteria [9][10][11][12] or plants known for their ability to immobilize heavy metals in the cell wall and to compartmentalize them in vacuoles [13]. Interestingly, polyextremophilic algae have intrinsic properties that make them capable of selective removal and concentration of metals, thanks to their adaptation to live in geothermal and volcanic sites [14][15][16][17]. Geothermal fluids leach out of hot volcanic rocks and are enriched by enormous amounts of minerals and metals, including lithium, sulphur, boric acid, and precious metals such as gold, platinum, palladium, and silver [18].…”
Section: Introductionmentioning
confidence: 99%
“…The Cyanidioschyzon and Cyanidium species are obligatory autotrophs, while the Galdieria species can grow auto-, mixo-, and heterotrophically and tolerate high concentrations of salts [21]. This makes Galdieria particularly suitable for biotechnological applications [14]. The ability of Galdieria sulphuraria to recover REEs has already been assessed [5,22] and confirmed by an approved patent [23].…”
Section: Introductionmentioning
confidence: 99%